Susceptibility of Young Sheep to Oral Infection with Bovine Spongiform Encephalopathy Decreases Significantly after Weaning - Hunter, Nora (American Society for Microbiology, 2012)
Bovine spongiform encephalopathy (BSE) is a transmissible spongiform encephalopathy (TSE) (or prion disease) that is readily transmissible to sheep by experimental infection and has the shortest incubation period in animals with the ARQ/ARQ PRNP genotype (at codons 136, 154, and 171). Because it is possible that sheep in the United Kingdom could have been infected with BSE by being fed contaminated meat and bone meal supplements at the same time as cattle, there is considerable interest in the responses of sheep to BSE inoculation. Epidemiological evidence suggests that very young individuals are more susceptible to TSE infection; however, this has never been properly tested in sheep. In the present study, low doses of BSE were fed to lambs of a range of ages (∼24 h, 2 to 3 weeks, 3 months, and 6 months) and adult sheep. The incidence of clinical BSE disease after inoculation was high in unweaned lambs (∼24 h and 2 to 3 weeks old) but much lower in older weaned animals The incubation period was also found to be influenced by the genotype at codon 141 of the PRNP gene, as lambs that were LF heterozygotes had a longer mean incubation period than those that were homozygotes of either type. The results suggest that sheep in the United Kingdom would have been at high risk of BSE infection only if neonatal animals had inadvertently ingested contaminated supplementary foodstuffs.